Collaborative Writing Technique (CWT): Elevators Students’ Writing Performance - Nurjanah, Siti; Firdaus, Masagus; Mulyadi, Mulyadi (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aimed to improve the students’ writing skill and their activeness through collaborative writing technique (CWT). The subject were 25 students of phase E at SMA Insan Cendikia Sriwijaya Palembang in academic year 2023/2024. Data collection technique used writing test and observation. This study is classroom action research (CAR) which was conducted into three cycles. Each cycle consisted of four stages; planning, action, observation and reflection. The result in Cycle I, the average score is 68.08 with the classical achievement 52%. In Cycle II, the average score is 79.44 with the classical achievement 76%. The last, Cycle III has 87.24 average score with 92% as the classical achievement. Those increasement obtained the success criteria of this study. In conclusion, the implementation of CWT could improve the phase E students’ writing skill at SMA Insan Cendikia Sriwijaya Palembang.